A congestion‐aware mixed integer linear programming model for placement and scheduling of quantum circuits with a two‐level heuristic solution approach. Issue 1 (22nd December 2020) - Bahreini, Tayebeh; Mohammadzadeh, Naser
Abstract: In recent years, many studies have been focused on designing quantum circuits for the promising future of quantum computers. In these studies, latency has been considered as one of the main performance measures in quantum circuit design. This paper proposes a congestion‐aware mixed integer linear programming model for placement and scheduling of quantum circuits. The proposed model determines initial locations for qubits and locations for gates, and schedules the movement of qubits along the channels in such a way that the total latency is minimized. Since finding the optimal solution of the model for large circuits within a reasonable amount of time is not practical, a heuristic solution method has been developed for the proposed model. Moreover, some experiments are conducted to evaluate the performance of the proposed model and the solution approach. Experimental results show that the proposed approach improves the average latency by about 14.5% for the attempted benchmarks compared with the best in the literature.